Glass ceramic with excellent acid and alkali resistance as well as preparation method and application of glass ceramic

By strictly controlling the relationship between oxide components and content in microcrystalline glass, the problem of insufficient chemical durability of microcrystalline glass in the prior art is solved, and excellent acid and alkali resistance and high strength are achieved, which are suitable for display panels of smart electronic products.

CN119661084APending Publication Date: 2025-03-21CHONGQING AUREAVIA HI TECH GLASS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411812729.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-22
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art does not have outstanding effects when improving the chemical durability of microcrystalline glass, and increases the number of process times and costs, affecting the monomer strength and drop resistance of the glass.

Method used

By strictly controlling the range and content relationship of oxide components in the microcrystalline glass of lithium aluminum silicon system, for example, adjusting the content of oxides such as SiO2, Al2O3, P2O5, ZrO2, and setting the ratio of alkali metal and alkaline earth metal under a specific crystallinity degree to obtain excellent acid and alkali resistance.

Benefits of technology

It achieves excellent acid and alkali resistance of microcrystalline glass, while maintaining high strength and good light transmission, meeting the needs of smart electronic products in acid and alkali environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661084A_ABST
    Figure CN119661084A_ABST
Patent Text Reader

Abstract

The invention relates to microcrystalline glass with excellent acid and alkali resistance as well as a preparation method and application thereof. The glass according to the invention comprises the following components in mole percentages relative to the total mole number of the components of the glass: 67.0% < = SiO2 < = 71.0%; al2O3 is greater than or equal to 3.5% and less than or equal to 4.5%; 0.7% < = P2O5 < = 1.5%; zrO2 is greater than or equal to 1.5% and less than or equal to 4.0%; 0% < Na2O < = 1.0%; 0% < K2O < = 0.5%; 20.0% < = Li2O < = 23.0%; 0% < CaO < = 1.8%; 0% < B2O3 < = 0.7%; 0% < = MgO < = 1.0%; and 0% < = BaO < = 0.8%. After standing in a hydrochloric acid solution, a hydrofluoric acid solution and / or a sodium hydroxide solution, the glass ceramic disclosed by the invention is very low in weight loss per unit area, excellent in acid and alkali resistance and excellent in strength after strengthening, and the tensile stress linear density CTLD reaches 45000-64000 MPa / mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to glass-ceramics and products, and more specifically, to lithium aluminum silicate glass-ceramics compositions and products with high acid and alkali resistance. This invention patent application is a divisional application of the invention patent application with application number 202210869861.8, application date July 22, 2022, and invention name "A glass-ceramic with excellent acid and alkali resistance, preparation method and use thereof". Technical Background

[0002] With the continuous development and progress of smart electronic products, the requirements for cover glass used in display technology are also increasing. In the processing of microcrystalline glass, it is necessary to ensure that the corrosion of the glass by acid and alkali cleaning will not affect the optics, strength, and subsequent processing of the glass, while meeting the requirements of electronic products used in acid and alkali environments, such as hand-held sweating, etc. In the prior art, in order to ensure the strength of the glass, the drop resistance and impact resistance of the glass, it is usually necessary to chemically strengthen the microcrystalline glass. During the strengthening process, small ions (such as Li + , Na + ) and large ions (Na + , K + ) exchange, the glass surface is more susceptible to acid and alkali etching and other damages due to the rich sodium ions.

[0003] To address this problem, the existing technology usually reduces the Na + Concentration, to improve the chemical durability of microcrystalline glass from a process perspective. For example: Application No. CN202110739360.3 provides a strengthening method, firstly performing primary strengthening in a 100wt% sodium salt (such as sodium nitrate) salt bath, using sodium ions to exchange lithium ions in the microcrystalline glass, and then placing the primary strengthened microcrystalline glass in a secondary strengthening salt bath containing lithium salts, and a potassium salt (such as potassium nitrate) salt bath with a certain amount of lithium ions for secondary strengthening to reduce the sodium ion component on the surface of the microcrystalline glass after strengthening. For another example, application No. CN201980020541.1 provides a range of ion exchange depths for glass ceramics after chemical strengthening, the relationship between the maximum surface compressive stress and the maximum central tension, and the Na2O concentration of glass ceramic products at the outer surface is less than 10mol%. Summary of the invention

[0004] The existing technology for improving the chemical durability of microcrystalline glass does not have a significant effect on improving the chemical durability, and will essentially increase the number of strengthening processes and increase costs; on the other hand, it will lose a certain strengthening effect and have a negative impact on the monomer strength, drop resistance and other properties of the microcrystalline glass.

[0005] In order to improve the environmental durability or chemical durability of microcrystalline glass and improve the acid and alkali resistance of microcrystalline glass, the present invention strictly controls the range of oxide components and the content relationship between oxides in the microcrystalline glass of lithium aluminum silicon system, such as: in order to improve the melting effect and the adverse effect of excessive grain size on optics after crystallization treatment, the amount of B2O3, Na2O and P2O5 is controlled at the same time; at a specific crystallinity, the ratio of alkali metal and alkaline earth metal is set, etc., to obtain microcrystalline glass with excellent acid and alkali resistance. The national standard document used for acid and alkali resistance test is: GB / T 32644-2016 "Test method for chemical durability of flat panel display substrate glass".

[0006] In order to solve the above-mentioned prior art problems, the present invention provides the following technical solutions:

[0007] 1. An acid- and alkali-resistant glass-ceramic, characterized in that it comprises the following components in molar percentage relative to the total molar number of each component of the glass:

[0008] 67.0%≤SiO2≤71.0%;

[0009] 3.5%≤Al2O3≤4.5%;

[0010] 0.7%≤P2O5≤1.5%;

[0011] 1.5%≤ZrO2≤4.0%;

[0012] 0%<Na2O≤1.0%;

[0013] 0%<K2O≤0.5%;

[0014] 20.0%≤Li2O≤23.0%;

[0015] 0%<CaO≤1.8%;

[0016] 0%<B2O3≤0.7%;

[0017] 0% ≤ MgO ≤ 1.0%; and

[0018] 0%≤BaO≤0.8%.

[0019] 2. The glass-ceramics according to technical solution 1 is characterized in that the component content of the glass-ceramics meets the following limiting conditions:

[0020] 10≥(Na2O+K2O+Li2O) / ZrO2≥0.2, preferably 10≥(Na2O+K2O+Li2O) / ZrO2≥5; and / or

[0021] CaO+BaO+MgO≥1.5×(Na2O+K2O); and / or

[0022] ZrO2+P2O5≥7.6×B2O3.

[0023] 3. The microcrystalline glass according to technical solution 1 is characterized in that, based on the molar percentage of the total molar number of each component of the glass, 1.0%≤P2O5≤1.5%, and / or 2.0%≤ZrO2≤3.0%, and / or 0%<CaO≤1.5%.

[0024] 4. The glass-ceramics according to technical solution 1 is characterized in that the glass-ceramics comprises the following components in molar percentage relative to the total molar number of each component of the glass:

[0025] 68.0%≤SiO2≤69.5%;

[0026] 3.8%≤Al2O3≤4.3%;

[0027] 1.0%≤P2O5≤1.5%;

[0028] 2.5%≤ZrO2≤3.0%;

[0029] 0.1%≤Na2O≤1.0%;

[0030] 0.1%≤K2O≤0.3%;

[0031] 20.5%≤Li2O≤21.5%;

[0032] 0.5%≤CaO≤1.5%;

[0033] 0.1%≤B2O3≤0.4%;

[0034] 0% ≤ MgO ≤ 1.0%; and

[0035] 0%≤BaO≤0.8%.

[0036] 5. The glass-ceramics according to technical solution 1 is characterized in that, in terms of molar percentage relative to the total molar number of each component of the glass, the glass-ceramics comprises:

[0037] The value of SiO2 / (Li2O+Al2O3) is 2.5-3.0; and / or

[0038] The value of (CaO+BaO+MgO) / ZrO2 is 0.2-0.7.

[0039] 6. The microcrystalline glass according to Technical Solution 1 is characterized in that the microcrystalline glass contains a crystalline phase, and the main crystalline phases in the crystalline phase are lithium disilicate crystalline phase and petalite crystalline phase.

[0040] 7. The microcrystalline glass according to Technical Solution 6 is characterized in that the crystalline phase accounts for at least 80.00wt% of the microcrystalline glass.

[0041] 8. The microcrystalline glass according to Technical Solution 6 is characterized in that the average size of the grains in the microcrystalline glass is 10-50nm, preferably 10-30nm.

[0042] 9. The microcrystalline glass according to Technical Solution 6 is characterized in that, at a thickness of 0.7 mm, for light of a wavelength of 550 nm, the microcrystalline glass is transparent and has a transmittance of not less than 90.00%.

[0043] 10. The glass-ceramics according to any one of technical solutions 1 to 9, characterized in that the unstrengthened glass-ceramics are placed in:

[0044] After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x1, x1<0.050 mg / cm 2 and / or,

[0045] After being placed in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x2, x2≤8.00 mg / cm 2 ;

[0046] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x3 is, x3≤0.20 mg / cm 2 .

[0047] 11. The microcrystalline glass according to Technical Solution 8 is characterized in that the microcrystalline glass includes a compressive stress layer formed by ion exchange, and the depth DOL_0 of the compressive stress layer on any surface of the microcrystalline glass is 15%-25% of the thickness of the microcrystalline glass.

[0048] 12. The microcrystalline glass according to technical solution 11 is characterized in that the tensile stress line density CT_LD of the microcrystalline glass is 45000MPa / mm-64000MPa / mm.

[0049] 13. The microcrystalline glass according to technical solution 11 is characterized in that the surface compressive stress of the microcrystalline glass is 350MPa-500MPa.

[0050] 14. The microcrystalline glass according to technical solution 11 is characterized in that the |CT_AV| of the microcrystalline glass is 80MPa-110MPa.

[0051] 15. The glass-ceramic according to any one of technical solutions 11-14 is characterized in that, when placed in a hydrochloric acid solution with a mass concentration of 5% at 95° C. for 24 hours, the weight loss per unit area of ​​the glass-ceramic x4 is, x4<0.150 mg / cm 2 , preferably x4<0.100mg / cm 2 and / or,

[0052] After standing in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x5, x5≤8.50mg / cm 2 ;

[0053] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x6 is, x6≤0.25 mg / cm 2 .

[0054] 16. A method for preparing glass-ceramics, comprising the following steps:

[0055] (1) Preparation of substrate glass: Mixing various raw materials into a melt and forming the mixture, and then annealing the mixture to obtain substrate glass;

[0056] (2) Preparation of glass-ceramic bricks: heating the substrate glass obtained in step (1) to perform nucleation treatment and crystallization treatment in sequence to obtain glass-ceramic bricks;

[0057] (3) Cold processing: The microcrystalline glass brick obtained in step (2) is subjected to cold processing to obtain a microcrystalline glass sample as described in any one of technical solutions 1 to 10.

[0058] Among them, the cold processing treatment may include slicing treatment. Before slicing treatment, the microcrystalline glass bricks may be shaped, and after slicing treatment, they may be CNC treated, ground, and polished in sequence, or after slicing treatment, at least one of CNC treatment, grinding, and polishing treatment may be selected to modify the glass sheets.

[0059] 17. The preparation method according to technical solution 16, further comprising the following steps:

[0060] (4) Chemically strengthen the glass-ceramic sample obtained in step (3) to obtain a glass-ceramic sample as described in any one of technical solutions 11-15.

[0061] 18. The preparation method according to technical solution 16 or 17, wherein in step (1), the melting temperature is 1500°C to 1650°C; and the annealing temperature is 450°C to 550°C.

[0062] 19. The preparation method according to technical solution 16 or 17, wherein in step (2), the nucleation treatment is performed at 530-565°C for 90-240 min; and the crystallization treatment is performed at 640-700°C for 90-240 min.

[0063] 20. The preparation method according to technical solution 16 or 17, wherein in step (2), the crystallization treatment is a semi-crystallization treatment, and after the semi-crystallization treatment makes the degree of crystallization of the substrate glass reach 1 / 3 to 4 / 5 of the degree of complete crystallization, a 3D hot bending treatment is further performed to obtain microcrystalline glass bricks; preferably, the 3D hot bending treatment is a hot bending treatment with three stages: preheating at a temperature of 450 to 720°C, hot bending at 720 to 820°C, and cooling to room temperature.

[0064] 21. A preparation method according to technical solution 17, wherein, in step (4), the chemical strengthening treatment is carried out in a mixed salt bath containing 30-100wt% NaNO3, preferably 30-90wt% NaNO3 and / or 0-70wt% KNO3, preferably 10-70wt% KNO3, and LiNO3 is added in an amount of 0.01-0.10wt% relative to the total weight of the mixed salt bath.

[0065] 22. The preparation method according to technical solution 21, wherein the chemical strengthening treatment performs one or more ion exchanges so that the tensile stress line density CT_LD of the microcrystalline glass reaches 45000-64000 MPa / mm.

[0066] 23. Microcrystalline glass obtained by the preparation method described in any one of Technical Solutions 16-22.

[0067] 24. Use of the microcrystalline glass described in any one of Technical Solutions 1 to 15 or the microcrystalline glass described in Technical Solution 23 in display panels or display screens for smart electronic products.

[0068] 25. Application of the microcrystalline glass described in any one of Technical Solutions 1 to 15 or the microcrystalline glass described in Technical Solution 23 in glass devices.

[0069] One of the above technical solutions has the following advantages or beneficial effects: the microcrystalline glass provided by the present invention or the microcrystalline glass obtained by the preparation method of the present invention has excellent acid and alkali resistance, as well as excellent strength and light transmittance.

[0070] The present invention uses non-chemically strengthened microcrystalline glass to place:

[0071] After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x1, x1<0.050 mg / cm 2 and / or,

[0072] After being placed in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x2, x2≤8.00 mg / cm 2 ;

[0073] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x3 is, x3≤0.20 mg / cm 2 .

[0074] The present invention uses chemically strengthened microcrystalline glass to place:

[0075] After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x4, x4<0.150 mg / cm 2 , preferably x4<0.100mg / cm 2 and / or,

[0076] After standing in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x5, x5≤8.50mg / cm 2 ;

[0077] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x6 is, x6≤0.25 mg / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 The crystallized wafer of Example S1 has a transmittance spectrum of light with a wavelength from 200 nm to 1000 nm.

[0079] Figure 2 The weight loss curves per unit area of ​​the crystallized sheets and the strengthened sheets of Examples S1-S10 and Comparative Examples D1-D9 were placed in a hydrochloric acid solution with a mass concentration of 5% at 95°C for 24 hours.

[0080] Figure 3 The weight loss curves per unit area of ​​the crystallized sheets and the strengthened sheets are shown in Examples S1-S10 and Comparative Examples D1-D9 after being placed in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes.

[0081] Figure 4 The weight loss curves per unit area of ​​the crystallized sheets and the strengthened sheets are shown in Examples S1-S10 and Comparative Examples D1-D9 after being placed in a sodium hydroxide solution with a mass concentration of 5% at 95°C for 6 hours. DETAILED DESCRIPTION

[0082] The present invention provides a transparent microcrystalline glass with excellent acid and alkali resistance and a preparation method thereof, so as to solve the problem that the microcrystalline glass has both acid and alkali resistance and strength.

[0083] Specifically, the present invention provides a glass-ceramic having excellent acid and alkali resistance, wherein the glass-ceramic composition comprises the following components in molar percentage relative to the total molar number of each component of the glass:

[0084] 67.0%≤SiO2≤71.0%;

[0085] 3.5%≤Al2O3≤4.5%;

[0086] 0.7%≤P2O5≤1.5%; preferably 1.0%≤P2O5≤1.5%;

[0087] 1.5%≤ZrO2≤4.0%, preferably 2.0%≤ZrO2≤3.0%;

[0088] 0%<Na2O≤1.0%;

[0089] 0%<K2O≤0.5%;

[0090] 20.0%≤Li2O≤23.0%;

[0091] 0%<CaO≤1.8%, preferably 0%<CaO≤1.5%;

[0092] 0%<B2O3≤0.7%;

[0093] 0% ≤ MgO ≤ 1.0%; and

[0094] 0%≤BaO≤0.8%.

[0095] SiO2 is an oxide that forms the network skeleton of glass. It is used to stabilize the network structure of glass and microcrystalline glass. In the lithium aluminum silicon system, it is used to form crystalline phases such as lithium disilicate, petalite, β-spodumene and quartz. When the substrate glass is heat-treated and converted into microcrystalline glass, the content of SiO2 should be high enough to form petalite and lithium disilicate. When the SiO2 content is too little, the glass has a tendency to have a higher thermal expansion coefficient and reduced thermal shock resistance; when the SiO2 content is too much, the glass has a poor solubility, or the viscosity of the molten glass liquid increases, making the glass liquid difficult to clarify, the difficulty of glass molding increases, the productivity decreases, and the time required for the crystallization of the glass increases. In some embodiments, the molar percentage of SiO2 is 67.0%-71.0%. In some embodiments, the molar percentage of SiO2 is 68.0%-69.5%. In some embodiments, the microcrystalline glass may include SiO2 in a molar percentage of 67.0% to 71.0%, 68.0% to 69.5%, 67.0% to 69.5%, 68.0% to 71.0%, 67.3% to 71.0%, 67.5% to 71.0%, 67.7% to 71.0%, 68.2% to 71.0%, 68.5% to 71.0%, 68.8% to 71.0%, 69.0% to 71.0%, 69.0% to 69.8%, 69.0% to 69.5%, and 69.0% to 69.3%. In some embodiments, the microcrystalline glass may contain SiO2 with a molar percentage of 67.0%, 67.1%, 67.2%, 67.3%, 67.4%, 67.5%, 67.6%, 67.7%, 67.8%, 67.9%, 68.0%, 68.1%, 68.2%, 68.3%, 68.4%, 68.5%, 68.6%, 68.7%, 68.8%, 68.9%, 69.0%, 69.1%, 69.2%, 69.3%, 69.4%, 69.5%, 69.6%, 69.7%, 69.8%, 69.9% or 71.0%, or within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0096] Al2O3 is used to form the glass skeleton. Al2O3 is coordinated around the crystal nucleus to form a "center-shell" structure. This structure makes it difficult for the crystal nucleus components to be supplied from the outer part of the shell, and the crystal nucleus is not easy to grow, and it is easy to form multiple tiny grains. Al2O3 stabilizes the glass network structure, improves mechanical properties and chemical durability, and inhibits the phase separation of the glass, reduces the thermal expansion coefficient, and increases the strain point. When the Al2O3 content is too little, the glass has a tendency to increase its thermal expansion coefficient, its chemical durability is reduced, and the crystal nucleus becomes larger, and the crystallized glass is prone to white turbidity; when the Al2O3 content is too much, the glass's solubility becomes worse, production becomes difficult, and mullite crystals are easily precipitated to make the glass devitrified. The molar percentage of Al2O3 is 3.5%-4.5%. In some embodiments, the molar percentage of Al2O3 is 3.8%-4.3%. In some embodiments, the molar percentage of SiO2 can be 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4% or 4.5%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0097] Li2O is the main component of petalite and lithium disilicate crystals, and is also a necessary component for chemical strengthening. When the Li2O content is too little, the glass is prone to precipitate crystalline phases, such as mullite, which makes the glass devitrified, reduces its meltability or increases its viscosity, making it difficult to clarify and difficult to form; and when the Li2O content is too much, the crystallization ability of the glass becomes too strong, the glass has a tendency to devitrify, and the crystallized glass becomes easily broken. The molar percentage of Li2O is 20.0%-23.0%. In some embodiments, the molar percentage of Li2O is 20.5%-21.5%. In some embodiments, the molar percentage of Li2O can be 20.0%, 20.1%, 20.2%, 20.3%, 20.4%, 20.5%, 20.6%, 20.7%, 20.8%, 20.9%, 21.0%, 21.1%, 21.2%, 21.3%, 21.4%, 21.5%, 21.6%, 21.7%, 21.8%, 21.9%, 22.0%, 22.1%, 22.2%, 22.3%, 22.4%, 22.5%, 22.6%, 22.7%, 22.8%, 22.9% or 23.0%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0098] SiO2, Al2O3, and Li2O are the main components of the main crystalline phase lithium disilicate and petalite. In the network skeleton formed by SiO2, Li2O and Al2O3 compensate each other's charges and dissolve in the network skeleton. The molar percentage range of SiO2 / (Li2O+Al2O3) is controlled to be 2.5-3.0, 2.6-3.0, 2.7-3.0, 2.8-3.0 or 2.9-3.0; it can also be 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired performance of the present invention can be obtained.

[0099] P2O5 is a glass-forming oxide. It exists in the network structure as phosphorus-oxygen tetrahedron [PO4]. P2O5 has a fluxing effect and has the dispersion coefficient of glass and the ability to transmit ultraviolet light. It effectively inhibits the precipitation of coarse ZrO2 crystals. When the P2O5 content is too little, the precipitated coarse ZrO2 crystals make the glass devitrified; when the P2O5 content is too much, the precipitated microcrystal content is reduced, and the thermal expansion coefficient of the glass tends to become high. The molar percentage of P2O5 is 0.7%-1.5%, preferably 1.0%-1.5%. In some embodiments, the molar percentage of P2O5 can be 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired performance of the present invention can be obtained.

[0100] Na2O is an oxide outside the glass network. It can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, break bonds, increase the thermal expansion coefficient of the glass, and play an important role in adjusting the grain size, crystal phase composition, and crystal phase ratio. Reducing the content of Na2O can improve the thermal stability, chemical stability, and mechanical strength of the glass, so the weather resistance of the glass will be improved. However, if Na2O is to be completely removed, the strengthening time will be longer, the strengthening efficiency will be reduced, and the strengthening effect will be affected. Moreover, after removing Na2O, other raw materials need to be added, which will increase the manufacturing cost. Based on this, a certain amount of Na2O needs to be present in the glass, that is, the amount of Na2O must be greater than 0%, so the molar percentage of Na2O is 0-1.0% (not 0). In some embodiments, the molar percentage of Na2O can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0101] K2O is also a network external oxide. + Radius larger than Na + Therefore, adding K2O can reduce the tendency of glass to crystallize and increase the transparency and gloss of the glass. However, when the K2O content is too high, the crystallization ability of the glass becomes stronger, the glass is prone to devitrification, and the crystallized glass is prone to breakage. + The ionic radius is larger than that of Li + , it is not easy to enter the crystal, so the K +Remains in the glass phase. The molar percentage of K2O is 0-0.50% (not 0). In some embodiments, the molar percentage of K2O can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26 %, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49% or 0.50%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0102] ZrO2, as a nucleating agent for glass-ceramics, can improve the viscosity, hardness, elasticity, refractive index, chemical stability of glass, and reduce the thermal expansion coefficient of glass. ZrO2 can improve the stability of lithium aluminum silicon glass by significantly reducing the liquidus temperature and glass devitrification during the formation process. The increase of nucleating agent can form finer grains, but excessive ZrO2 will produce white zirconium precipitates when the glass is molten and poured, which is not conducive to the production of transparent glass-ceramics. By adjusting the content of P and Zr, nucleation can be promoted, the number of crystal nuclei can be increased, the size of crystals can be reduced, and good optical effects can be obtained in the presence of heterocrystalline phases. When the ZrO2 content is too little, the crystal nuclei cannot be fully formed, and coarse crystals are easily precipitated, making the glass turbid and devitrified. The molar percentage of ZrO2 is 1.5%-4.0%, preferably 2.0%-3.0%. In some embodiments, the molar percentage of ZrO2 can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4.0%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0103] B2O3 helps to lower the melting temperature of the base glass, and is conducive to obtaining an interlocking crystal microstructure in the microcrystalline glass, so that the damage resistance of the microcrystalline glass is improved. B2O3 has boron-oxygen triangles [BO3] and boron-oxygen tetrahedrons [BO4] as structural units. It can reduce the expansion coefficient of the glass and improve the thermal and chemical stability of the glass. When the amount of B2O3 added is too large, the thermal expansion coefficient of the glass increases due to the increase in the content of boron-oxygen triangles, and the boron anomaly occurs. When the boron in the residual glass phase is in a triangular coordination state, the tri-coordinated boron-oxygen triangle is not as strong as the boron-oxygen tetrahedron, and the effect of opening the network structure will appear. Therefore, the boron in the residual glass phase will reduce the viscosity of the residual glass phase, which will promote the growth of lithium silicate crystals, especially the growth of larger crystals. At the same time, a large number of boron-oxygen triangles in the microcrystalline glass will show larger Vickers indentation cracks. In addition, when the B2O3 content is high, the chemical durability of the glass will deteriorate. The molar percentage of B2O3 is 0-0.7% (not 0). In some embodiments, the mole percentage of B2O3 can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, %. 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69% or 0.70%, or any proportion within the numerical range formed by any two of the above specific numerical values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0104] CaO can increase the chemical stability and mechanical strength of glass. CaO can reduce the viscosity of glass, improve the solubility and formability of glass, and can also be used to adjust the thermal expansion coefficient and refractive index of microcrystalline glass. When the CaO content is too much, the glass is easy to lose transparency after crystallization. Excessive CaO residues in the glass phase produce a refractive index difference with the main crystal phase, reducing the optical properties of microcrystalline glass. The molar percentage of CaO is 0-1.8% (not 0), preferably 0-1.5% (not 0). In some embodiments, the molar percentage of CaO may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0. 67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1. 02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49%, 1.50%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.60%, 1.61 %, 1.62%, 1.63%, 1.64%, 1.65%, 1.66%, 1.67%, 1.68%, 1.69%, 1.70%, 1.71%, 1.72%, 1.73%, 1.74%, 1.75%, 1.76%, 1.77%, 1.78%, 1.79% or 1.80%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained. .

[0105] MgO can partially enter petalite, which can slow down the hardening speed of glass and improve the forming properties of glass. MgO can also reduce the crystallization tendency and crystallization speed, increase the high temperature viscosity of glass, and improve the chemical stability and mechanical strength of glass. When the MgO content is too little, the thermal expansion coefficient of glass tends to decrease, the crystallinity becomes stronger, and the microcrystalline glass is prone to devitrification. The molar percentage of MgO is 0-1.0%. In some embodiments, the molar percentage of MgO can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.6 4%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51 %, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78% %, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99% or 1.00%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0106] BaO is a component that reduces the viscosity of glass, improves the solubility and formability of glass, and can also be used to adjust the thermal expansion coefficient and refractive index of microcrystalline glass. The molar percentage of BaO is 0-0.8%. In some embodiments, the molar percentage of BaO can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 10.20%, 10.30%, 10.40%, 10.50%, 10.60%, 10.70%, 10.80%, 10.90%, 11.11%, 11.12%, 11.13%, 11.14%, 11.15%, 11.16%, 11.17%, 11.18%, 11.19%, 11.20%, 11.21%, 11.22%, 11.23%, 11.24%, 11.25%, 11.26%, 11.27%, 11.28%, 11.29%, 11.30%, 11.31%, 11.32%, 11.33%, 11.34%, 11.35%, 11.36%, 11.37%, 11.38%, 11.39%, 11.40%, 11.41%, 11.42%, 11.43%, 11.44%, 11.45%, 11.46%, 11.47%, 11.48%, 1 9%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41 %, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63% %, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79% or 0.80%, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0107] CaO, BaO, and MgO are components that improve the solubility and formability of glass. When these components are excessive, the low-temperature viscosity will be reduced; ZrO2 functions as a nucleating agent, crystallizes first at the initial stage of crystallization, and has the effect of inhibiting the flow of residual glass phase. In order to obtain microcrystalline glass with the same shape and characteristics, the molar ratio of (CaO+BaO+MgO) / ZrO2 is controlled to be 0.2-0.7. In some embodiments, the molar ratio of (CaO+BaO+MgO) / ZrO2 can be controlled to any ratio of 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7, or it can be controlled to any ratio within the numerical range consisting of any two of the above specific values ​​as endpoints.

[0108] Na2O, K2O, CaO, BaO, and MgO are alkaline earth metals and alkali metals, which have a great influence on the chemical durability of glass. The CaO+BaO+MgO in the glass phase is controlled to be ≥1.5×(Na2O+K2O).

[0109] Since Li2O, Na2O, and K2O alkali metal oxides play a fluxing effect in the system, and Li is an indispensable part of the main crystalline phases of petalite and lithium disilicate, ZrO2, as a nucleating agent in the system, should satisfy 10≥(Na2O+K2O+Li2O) / ZrO2≥0.2 with the alkali metal oxides, preferably 10≥(Na2O+K2O+Li2O) / ZrO2≥5, and more preferably 9≥(Na2O+K2O+Li2O) / ZrO2≥7, in order to achieve the best melting effect and ideal crystallinity and crystal phase content.

[0110] In some embodiments, the component contents of the glass-ceramics meet the following limiting conditions:

[0111] ZrO2+P2O5≥7.6×B2O3.

[0112] In some embodiments, the glass-ceramics comprises the following components in molar percentage relative to the total moles of the components of the glass:

[0113] 68.0%≤SiO2≤69.5%;

[0114] 3.8%≤Al2O3≤4.3%;

[0115] 1.0%≤P2O5≤1.5%;

[0116] 2.5%≤ZrO2≤3.0%;

[0117] 0.1%≤Na2O≤1.0%;

[0118] 0.1%≤K2O≤0.3%;

[0119] 20.5%≤Li2O≤21.5%;

[0120] 0.5%≤CaO≤1.5%;

[0121] 0.1%≤B2O3≤0.4%;

[0122] 0% ≤ MgO ≤ 1.0%; and

[0123] 0%≤BaO≤0.8%.

[0124] In some embodiments, the microcrystalline glass contains a crystal phase, and the main crystal phases in the crystal phase are lithium disilicate crystal phase and petalite crystal phase. It is accompanied by possible impurities, such as quartz, spodumene, lithium metasilicate, etc. Lithium disilicate Li2Si2O5 is an orthorhombic crystal, and its crystals are often flat and have obvious dissociation surfaces. This crystal phase forces cracks to extend along the distorted grain boundaries due to its irregular orientation, reducing the possibility of crack extension. Petalite LiAlSi4O 10 It is a monoclinic crystal, Li and O are tetrahedral coordination, and petalite can be chemically strengthened in a salt bath. The Na + Substituting Li in petalite + .

[0125] In some embodiments, the crystalline phase accounts for at least 80.00wt% of the glass-ceramics, preferably 80wt% to 97wt%, and more preferably 85wt% to 96wt%. In some embodiments, the crystalline phase accounts for 80.00wt%, 81.00wt%, 82.00wt%, 83.00wt%, 84.00wt%, 85.00wt%, 86.00wt%, 87.00wt%, 88.00wt%, 89.00wt%, 90.00wt%, 91.00wt%, 92.00wt%, 93.00wt%, 94.00wt%, 95.00wt%, 96.00wt% or 97.00wt% of the glass-ceramics. Or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0126] In some embodiments, in the glass-ceramics, the average size of the crystal grains is 10-50 nm, preferably 10-30 nm. In some embodiments, the average size of the crystal grains can be 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 35, 38, 40, 45, 48 or 50 nm, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired performance of the present invention can be obtained.

[0127] In some embodiments, at a thickness of 0.7 mm, for light of a wavelength of 550 nm, the glass-ceramics is transparent and has a transmittance of not less than 90.00%, preferably not less than 90.20%, more preferably not less than 90.40%, more preferably not less than 90.60%, more preferably not less than 90.80%, more preferably not less than 91.00%, more preferably not less than 91.20%, more preferably not less than 91.40%, more preferably not less than 91.60%, more preferably not less than 91.80%, more preferably not less than 92.00%, more preferably not less than 92.20%, more preferably not less than 92.40%, more preferably not less than 92.60%, more preferably not less than 92.80%, more preferably not less than 93.00% 。

[0128] In some embodiments, the glass-ceramics includes a compressive stress layer formed by ion exchange, and the depth DOL_0 of the compressive stress layer on any surface of the glass-ceramics is 15%-25% of the thickness of the glass-ceramics. In some embodiments, the depth DOL_0 of the compressive stress layer on any surface of the glass-ceramics may be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25% of the thickness of the glass-ceramics, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. In some embodiments, the thickness of the glass-ceramics is 0.7 mm, and the depth DOL_0 of the compressive stress layer on any surface of the glass-ceramics is 105 μm-175 μm.

[0129] In the present invention, those skilled in the art can select the thickness of the strengthened glass-ceramics according to the requirements. For example, in some embodiments, the thickness of the glass-ceramics is 0.2-2 mm.

[0130] In some embodiments, the tensile stress line density CT_LD of the microcrystalline glass is 45000 MPa / mm-64000 MPa / mm. In some embodiments, the tensile stress line density CT_LD of the microcrystalline glass can be 45000MPa / mm, 46000MPa / mm, 47000MPa / mm, 48000MPa / mm, 49000MPa / mm, 50000MPa / mm, 51000MPa / mm, 52000MPa / mm, 53000MPa / mm, 54000MPa / mm, 55000MPa / mm, 56000MPa / mm, 57000MPa / mm, 58000MPa / mm, 59000MPa / mm, 60000MPa / mm, 61000MPa / mm, 62000MPa / mm, 63000MPa / mm or 64000MPa / mm, or the tensile stress line density of any value within the numerical range formed by any two of the above specific values ​​as endpoints.

[0131] In some embodiments, the surface compressive stress of the glass-ceramics is 350MPa-500MPa. In some embodiments, the surface compressive stress of the glass-ceramics can be 350MPa, 400MPa, 450MPa or 500MPa, or any value of the surface compressive stress within the numerical range formed by any two of the above specific values ​​as endpoints.

[0132] In some embodiments, the |CT_AV| of the glass-ceramics is 80 MPa-110 MPa. In some embodiments, the |CT_AV| of the glass-ceramics can be 80 MPa, 90 MPa, 100 MPa or 110 MPa, or any value of |CT_AV| within the numerical range formed by any two of the above specific values ​​as endpoints.

[0133] In addition, the present invention also provides a method for preparing microcrystalline glass, which comprises the following steps:

[0134] (1) Preparation of substrate glass: The raw material mixture is melted and formed, and then annealed to obtain the substrate glass. The forming methods include but are not limited to float, overflow, rolling and pouring. The melting temperature is 1500℃~1650℃; the annealing temperature is 450℃~550℃, and the temperature is kept for 12~24h. Taking Example S1 as an example, the ingredients are mixed according to the formula of S1 for 30 minutes. The total amount of the mixture is 1000g. After mixing, 5g of clarifier (NaCl) is added, and it is melted in a platinum crucible at 1650℃ for 5 hours. Then it is poured into a molding mold for molding. After cooling to 900℃, it is placed in a 500℃ annealing furnace for annealing for 12 hours. After that, it is cooled to room temperature with the furnace to obtain the substrate glass. The preparation of substrate glass in other embodiments is the same as that in Example S1.

[0135] (2) Preparation of microcrystalline glass bricks: The substrate glass obtained in step (1) is heated in sequence to perform nucleation treatment and crystallization treatment to obtain microcrystalline glass bricks. The substrate glass is heat treated in a precision annealing furnace. The heat treatment process includes nucleation and crystallization. The nucleation process is T g +△t℃ / 240min(T g Indicates the glass transition point temperature, 5℃≤△t≤50℃); the crystallization process is T g +△T1 / 90min~240min (where 70℃≤△T1≤170℃), and finally obtain microcrystalline glass bricks. Or after nucleation treatment, semi-crystallization treatment is performed, and the crystallization process is T g +△T2 / 90min~240min (wherein 70℃≤△T2≤150℃), in the semi-crystallization treatment, after the degree of crystallization of the base glass reaches 1 / 3~4 / 5 of the degree of crystallization required by the final microcrystalline glass product, 3D hot bending treatment is also carried out to obtain microcrystalline glass bricks.

[0136] In some embodiments, the nucleation treatment is performed at 530-565°C for 90-240 minutes; the crystallization treatment is performed at 640-700°C for 90-240 minutes. The nucleation treatment time here refers to the time for the crystallization furnace to be kept warm after the temperature is increased to the set nucleation temperature at a set heating rate. The crystallization treatment time here refers to the time for the crystallization furnace to be kept warm after the temperature is increased to the set crystallization temperature at a set heating rate.

[0137] In some embodiments, the crystallization treatment is a semi-crystallization treatment. In the semi-crystallization treatment, after the degree of crystallization of the substrate glass reaches 1 / 3 to 1 / 2 of the degree of crystallization required for the final microcrystalline glass product, a 3D hot bending treatment is performed to obtain microcrystalline glass bricks; preferably, the 3D hot bending treatment is performed in three stages: preheating at a temperature of 450 to 720°C, hot bending at 720 to 820°C, and cooling to room temperature.

[0138] (3) Cold working:

[0139] The microcrystalline glass bricks obtained in step (2) are subjected to cold working treatment, wherein the cold working treatment includes slicing treatment. Before slicing treatment, the microcrystalline glass bricks can be shaped, and after slicing treatment, they can be subjected to CNC treatment, grinding treatment, and polishing treatment in sequence, or after slicing treatment, at least one of CNC treatment, grinding treatment, and polishing treatment is selected to perform glass sheet modification treatment to obtain microcrystalline glass samples (i.e., crystallized sheets), such as microcrystalline glass samples of about 50mm*50mm*0.7mm.

[0140] After steps (1) to (3), a glass-ceramic sample (without chemical strengthening) can be prepared. The glass-ceramic sample prepared here has excellent acid and alkali resistance after testing. The specific test results are as follows:

[0141] After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x1, x1<0.050 mg / cm 2 and / or,

[0142] After being placed in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x2, x2≤8.00 mg / cm 2 ;

[0143] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x3 is, x3≤0.20 mg / cm 2 .

[0144] In some preferred embodiments, the following steps are also included:

[0145] (4) Chemical strengthening treatment: The glass-ceramic sample (i.e., crystallized sheet) obtained in step (3) is placed in a high-temperature salt bath at 350°C to 550°C, wherein the salt bath composition is 30-100wt% NaNO3 (preferably 30-90wt% NaNO3) and / or 0-70wt% KNO3 (preferably 10-70wt% KNO3), and LiNO3 is added in an amount of 0.01-0.10wt% relative to the total weight of the salt bath, and one or more ion exchanges are performed to obtain a strengthened glass-ceramic (i.e., strengthened sheet). The tensile stress linear density of the glass-ceramic can reach between 45,000 and 64,000 MPa / mm.

[0146] After the chemical strengthening treatment in step (4), a compressive stress layer is formed on the surface of the microcrystalline glass due to ion exchange, and the depth DOL_0 of the compressive stress layer on any surface of the microcrystalline glass is 15%-25% of the thickness of the microcrystalline glass.

[0147] The glass-ceramics containing the compressive stress layer obtained in step (4) is tested and still has excellent acid and alkali resistance. The specific test results are as follows:

[0148] After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x4, x4<0.150 mg / cm 2 and / or,

[0149] After standing in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x5, x5≤8.50mg / cm 2 ;

[0150] and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x6 is, x6≤0.25 mg / cm 2 .

[0151] 3. Application of the glass-ceramics of the present invention

[0152] The microcrystalline glass provided by the present invention can be used in display panels or display screens of smart electronic products, such as mobile phones, monitors, tablet computers, electronic watches, smart bracelets, smart watches, televisions, and smart glasses.

[0153] The glass-ceramics provided by the present invention can also be used in glass devices.

[0154] In all descriptions of the present invention, relevant details are set forth for understanding the present invention. All technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs. The specific details are as follows:

[0155] Explanation of terms

[0156] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.

[0157] Refractive index: The ratio of the speed of light in a vacuum to the speed of light in the medium.

[0158] In the embodiments and comparative examples of the present invention, the transmittance of the glass-ceramics at a wavelength of 550 nm is the average transmittance of multiple glass samples of the same batch measured at a wavelength of 550 nm. At least 5 samples of each batch of glass-ceramics are taken for testing.

[0159] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.

[0160] Crystallization: Glass grows a certain crystal based on the crystal nucleus through heat treatment.

[0161] b value: indicates the yellow-blue value of the material. In the present invention, the b value is the b value of transmitted light. A positive b value indicates that the material is blue. It is measured using a Konica Minolta spectrophotometer CM-3600A.

[0162] Base glass: glass that has not been subjected to nucleation, crystallization and strengthening treatments.

[0163] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.

[0164] CT_LD: tensile stress line density. The microcrystalline glass is placed in a salt bath for ion exchange to form a compressive stress layer (i.e., a strengthening layer). During the ion exchange process, a tensile stress layer is formed inside the glass. The tensile stress layer has an upper boundary that is spaced a certain distance from the upper surface of the strengthened microcrystalline glass and a lower boundary that is spaced a certain distance from the lower surface of the strengthened glass. The tensile stress line density of the microcrystalline glass after chemical strengthening can reach 45000MPa / mm-64000MPa / mm. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.

[0165] |CT_AV|: Absolute value of average tensile stress, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer, obtained by SLP-2000 stress meter test.

[0166] DOL_0: Depth of compressive stress layer, which refers to the distance from any surface of the glass-ceramic to the position close to the surface where the compressive stress is zero, obtained by testing with the SLP-2000 stress meter.

[0167] Surface compressive stress: surface CS. After chemical strengthening of glass ceramics, the alkali metal ions with smaller surface radius are replaced by alkali metal ions with larger radius. Due to the crowding effect of the alkali metal ions with larger radius, compressive stress is generated on the glass surface, which is called surface compressive stress. Surface CS is obtained by SLP-2000 stress meter test.

[0168] SOC: Photoelastic coefficient. Photoelasticity mainly refers to the phenomenon of anisotropy and birefringence of transparent materials after being subjected to force. The value of the residual stress (MPa) inside the material can be obtained by measuring the photoelastic coefficient and birefringence.

[0169] Instruments and test methods

[0170] Glass thickness: Determined by micrometer test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.

[0171] Crystal content test: The microcrystalline glass sample is tested by an X-ray diffractometer to obtain an XRD diffraction peak curve, and then the X-ray diffractometer (Shimadzu XRD-6000) test result file (RAW format) is imported into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), and the crystal content in the microcrystalline glass sample can be obtained by fitting and calculating. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6000, and the diffraction angle range used in the test is 2θ=10~50°, the scanning speed is 6° / min, the operating voltage is 40KV, and the operating current is 30mA.

[0172] The method for obtaining the average grain size is: using an X-ray diffractometer to test the microcrystalline glass sample, and using the Scherrer formula D = Kλ / (βcosθ) for the result data obtained from the XRD test, where λ is the X-ray wavelength, β is the peak half-height width, and K = 0.89, the average grain size can be obtained.

[0173] Transmittance and b-value test: According to the standard of GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, professional testing instruments are used to test the transmittance and b-value of microcrystalline glass. The testing instruments used in the present invention are Konica Minolta CM-3600A spectrophotometer and Shimadzu UV-2000 ultraviolet visible spectrophotometer.

[0174] Surface compressive stress (surface CS), DOL_0, |CT_AV| testing: using Japan Luceo (Japan Orihara) stress meter SLP-2000 for testing, light source wavelength of 518nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.54, exposure time: 300μsec.

[0175] When testing the surface CS, |CT_AV|, and DOL_0, it is necessary to drop a special refractive liquid on the stress meter, then wipe the strengthened micro-ceramic glass product clean, place it on the test path, and test its value. The refractive index of the refractive liquid used by SLP-2000 is 1.51.

[0176] CT_LD is related to the thickness of the glass sheet, the strengthening depth and the average tensile stress, and can be used to evaluate the drop resistance of the glass sheet. The CT_LD satisfies the following formula:

[0177]

[0178] Wherein d represents the thickness of the microcrystalline glass sheet (the glass thickness in the following embodiments and comparative examples of the present invention is 0.7 mm), unit: mm; DOL_0 represents the depth of the compressive stress layer, unit: μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in calculation, unit: MPa.

[0179] The acid and alkali resistant microcrystalline glass and the preparation method thereof of the present invention are described in detail below through specific embodiments.

[0180] Example S1:

[0181] (1) Preparation of substrate glass: Mix the raw materials according to the formula ratio of Example S1 in Table 1-1 below for 30 minutes. The total amount of the mixture is 1000 g. After mixing, add 5 g of clarifier (NaCl) and melt in a platinum crucible at 1650°C for 5 hours. Then pour into a molding mold for molding. After cooling to 900°C, put it into a 500°C annealing furnace for annealing for 12 hours. After that, cool it to room temperature with the furnace (cool to room temperature at a rate of about 5°C / min) to obtain the substrate glass. It is observed that the appearance of the substrate glass is transparent.

[0182] (2) Preparation of microcrystalline glass bricks: The substrate glass is heat treated in a precision annealing furnace. The heat treatment process includes two parts: nucleation and crystallization. The heat treatment process conditions are detailed in Table 1-1. The nucleation treatment temperature of Example S1 is 545°C (heating from room temperature to the nucleation treatment temperature at a heating rate of 10°C / min), and the treatment time is 240 min; the temperature is heated from the nucleation treatment temperature to the crystallization treatment temperature of 675°C at a heating rate of 10°C / min, and the treatment time is 90 min, and finally the required microcrystalline glass bricks are obtained.

[0183] (3) Cold processing: The microcrystalline glass bricks obtained in step (2) are trimmed by a grinding and polishing machine, and then cut into pieces by a multi-wire cutting machine. The CNC machine tool is used to process the microcrystalline glass samples of the desired size, such as a glass sheet with a length, width and thickness of 50mm*50mm*0.7mm. Then, a flat grinder and a polishing machine are used to perform rough grinding and polishing respectively to obtain microcrystalline glass sample pieces (referred to as "crystallized pieces", also called "crystallized glass").

[0184] The obtained crystallized sheet was tested for 550nm light transmittance and crystal phase. The specific test results are shown in Table 1-1. It can be seen from Table 1-1 that the 550nm transmittance is 91.54%. After testing, it is confirmed that the crystal phases Li2Si2O5 and LiAlSi4O 10 .

[0185] The present invention also uses Shimadzu UV-2000 ultraviolet visible spectrophotometer to test the transmittance of the crystallized sheet under 200-1000nm wavelength light. Figure 1As shown in the figure, in the visible light wavelength, the transmittance of the crystallized sheet is higher and the transparency is better.

[0186] The acid and alkali resistance of the crystallized sheet was tested under the conditions shown in Table 2-1. The mass of the glass sample before and after the acid and alkali resistance test was weighed using an analytical balance (Shimadzu ATY124), and the weight loss per unit area was calculated to measure the acid and alkali resistance of the glass sample. Specifically, the mass of the glass sample before and after the acid and alkali resistance test was weighed using an analytical balance, and m0 and m1 were respectively. The area of ​​the glass sample was s, and the weight loss per unit area x = (m0-m1) / s. Specifically, the crystallized glass sheet obtained in Example S1 was immersed in the following three acid-base conditions to test its acid and alkali resistance: 1) standing in a 5% hydrochloric acid solution at 95°C for 24 hours (abbreviated as "HCl-5%-95°C-24h"); 2) standing in a 10% hydrofluoric acid solution at 20°C for 20 minutes (abbreviated as "HF-10%-20°C-20min"); 3) standing in a 5% sodium hydroxide solution at 95°C for 6 hours (abbreviated as "NaOH-5%-95°C-6h"); the test results are summarized in Table 2-1.

[0187] (4) Chemical strengthening treatment: The above-mentioned crystallized sheet is subjected to chemical strengthening treatment according to the conditions of Table 3-1. The crystallized glass sheet obtained in the specific embodiment S1 is placed in a 480°C high-temperature salt bath, and an ion exchange is performed using a salt bath composed of a mixed salt bath containing 70wt% NaNO3 and 30wt% KNO3, wherein 0.03wt% lithium nitrate relative to the total weight of the mixed salt bath is also added to the mixed salt bath to introduce lithium ions. The specific ion exchange time is 540 minutes, thereby obtaining the ion-exchanged strengthened microcrystalline glass (referred to as "strengthening sheet"), that is, the target microcrystalline glass product of the present invention.

[0188] The same method and conditions as in step (3) were used to test the acid and alkali resistance of the reinforcing sheet under three acid and alkali conditions, and the test results are summarized in Table 2-2. The reinforcing sheet was also subjected to stress performance testing using a stress meter SLP-2000, specifically including testing and / or calculation of surface CS (MPa), absolute value of average tensile stress |CT_AV| (MPa), depth of compressive stress layer DOL_0 (μm), and tensile stress line density CT_LD (MPa / mm), and the test results are summarized in Table 3-1.

[0189] The substrate glass, microcrystalline glass bricks, crystallized sheets and strengthening sheets of Examples S2-S10 and Comparative Examples D1-D9 were prepared by methods similar to Example S1, and related tests were completed.

[0190] The light transmittance, crystal phase test results and acid and alkali resistance test results of the crystallized sheet, the acid and alkali resistance test results and various stress performance test results of the strengthened sheet are detailed in Table 1-1, Table 1-2, Table 2-1, Table 2-2 and Table 3-1 respectively.

[0191] Table 1-1 Glass formulations of Examples S1-S10 and performance test results of crystallized sheets before strengthening

[0192]

[0193]

[0194] Table 1-2 Glass formulations and performance test results of crystallized sheets of comparative examples D1-D9

[0195]

[0196]

[0197] Table 2-1 Test results of acid and alkali resistance of crystallized wafers obtained in Examples S1-S10 and Comparative Examples D1-D9 (before chemical strengthening)

[0198]

[0199]

[0200] Table 2-2 Test results of acid and alkali resistance of the reinforced sheets obtained in Examples S1-S10 and Comparative Examples D1-D9

[0201]

[0202] Table 3-1 Strengthening conditions of crystallized glass in the embodiment and comparative example and test results of surface stress after strengthening

[0203]

[0204]

[0205] From the above performance test results of Examples S1-S10 and Comparative Examples D1-D9, it can be seen that:

[0206] 1. The glass-ceramic samples that have only been crystallized (crystallized sheets) show better acid and alkali resistance than the glass-ceramic samples that have been chemically strengthened (strengthened sheets).

[0207] 2. Example By adjusting the oxide components and controlling the content relationship between the oxides, the acid and alkali resistance of the microcrystalline glass is improved as a whole. Taking S1 and D1 as examples, the acid and alkali resistance improvement effect of the crystallized sheet was tested. Resistance to hydrochloric acid corrosion, 95°C, 24 hours per unit area weight loss, S1 is about 52% less than D1 (the calculation method here is: (area weight loss of D1-area weight loss of S1) / area weight loss of D1, multiplied by 100%, the following calculation method is the same); resistance to hydrofluoric acid corrosion, 20°C, 20 minutes per unit area weight loss, S1 is about 18.3% less than D1; resistance to sodium hydroxide alkali corrosion, 95°C, 6 hours per unit area weight loss, S1 is about 14.5% less than D1.

[0208] 3. Comparing the strengthened microcrystalline glass (strengthening sheet), taking S1 and D1 as examples, the acid and alkali resistance improvement effect of the strengthening sheet was tested: resistance to hydrochloric acid corrosion, 95°C, 24 hours per unit area weight loss, S1 reduced by about 60.9% compared with D1; resistance to hydrofluoric acid corrosion, 20°C, 20 minutes per unit area weight loss, S1 reduced by about 15.3% compared with D1; resistance to sodium hydroxide alkali corrosion, 95°C, 6 hours per unit area weight loss, S1 reduced by about 51.8% compared with D1.

[0209] Therefore, the present invention provides a microcrystalline glass with excellent acid and alkali resistance.

[0210] By testing the stress performance of the reinforcing sheet prepared in the embodiment with SLP-2000, it can be known that the surface CS of the reinforcing sheet prepared in the embodiment can reach about 453MPa, |CT_AV| can reach about 106MPa, and it is calculated that the tensile stress line density CT_LD of the embodiment can reach between 50000-64000MPa / mm.

Claims

1. An electronic product, characterized in that: The electronic product comprises glass-ceramics, wherein the glass-ceramics comprises a crystal phase, wherein the main crystal phases in the crystal phases are lithium disilicate crystal phases and petalite crystal phases; In the microcrystalline glass, the molar percentage of SiO2 is 67.0%-71.0%, the molar percentage of Al2O3 is 3.5%-4.5%, the molar percentage of B2O3 is greater than 0 and less than or equal to 0.7%, the molar percentage of Na2O is greater than 0 and less than or equal to 1.0%, the molar percentage of K2O is greater than 0 and less than or equal to 0.50%, the molar percentage of P2O5 is 0.7%-1.5%, the molar percentage of ZrO2 is 2.0%-3.5%, and the molar percentage of CaO is greater than 0 and less than or equal to 1.8%; In terms of molar percentage, the component content of the microcrystalline glass satisfies: 10≥(Na2O+K2O+Li2O) / ZrO2≥5.

2. The electronic product according to claim 1, characterized in that: In terms of molar percentage, the component content of the microcrystalline glass satisfies: 9≥(Na2O+K2O+Li2O) / ZrO2≥7; and / or, ZrO2+P2O5≥7.6×B2O3.

3. The electronic product according to claim 1 or 2, characterized in that: In the glass-ceramics, the molar percentage of BaO is 0-0.8%, preferably the molar percentage of BaO is 0-0.50%, and the molar percentage of MgO is 0-1.0%, preferably the molar percentage of MgO is 0-0.80%; Preferably, in terms of molar percentage, the component content of the microcrystalline glass satisfies: CaO+BaO+MgO≥1.5×(Na2O+K2O), and / or the molar percentage ratio of (CaO+BaO+MgO) / ZrO2 is 0.2-0.7, preferably 0.2-0.5, and more preferably 0.2-0.

4.

4. The electronic product according to any one of claims 1 to 3, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 67.0%-69.5%, and / or, The molar percentage of Al2O3 is 3.8%-4.3%, and / or, The molar percentage of Li2O is 20.0%-23.0%, and / or, The molar percentage of B2O3 is 0.01%-0.50%, and / or, The molar percentage of Na2O is 0.01%-0.8%, and / or, The molar percentage of K2O is 0.01% to 0.30%, and / or, The molar percentage of P2O5 is 0.9%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.5%, and / or, The molar percentage of CaO is 0.01%-1.5%.

5. The electronic product according to claim 4, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 67.0%-68.0%, and / or, The molar percentage of Al2O3 is 4.0%-4.3%, and / or, The molar percentage of B2O3 is 0.01%-0.30%, and / or, The molar percentage of Na2O is 0.05%-0.3%, and / or, The molar percentage of K2O is 0.01%-0.20%, and / or, The molar percentage of P2O5 is 1.0%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.3%, and / or, The molar percentage of CaO is 0.10%-1.00%.

6. The electronic product according to any one of claims 1 to 5, characterized in that: In the glass-ceramics, the average size of the grains is 10-50 nm, preferably 10-30 nm; and / or, In the microcrystalline glass, the crystalline phase accounts for at least 80.00 wt % of the microcrystalline glass, preferably 80 wt % to 97 wt % of the microcrystalline glass, and more preferably 85 wt % to 96 wt % of the microcrystalline glass.

7. The electronic product according to any one of claims 1 to 6, characterized in that: When the thickness of the microcrystalline glass is 0.7 mm, for light with a wavelength of 550 nm, the microcrystalline glass is transparent and has a transmittance of not less than 90.00%, preferably not less than 90.20%, and more preferably not less than 90.40%.

8. The electronic product according to any one of claims 1 to 7, characterized in that: After the microcrystalline glass is subjected to chemical strengthening treatment, a strengthened microcrystalline glass is obtained, and the strengthened microcrystalline glass includes a compressive stress layer formed by ion exchange.

9. The electronic product according to claim 8, characterized in that: The depth DOL_0 of the compressive stress layer of the strengthened glass-ceramics is 15%-25% of the thickness of the glass-ceramics, preferably 20%-25%; and / or, The tensile stress linear density CT_LD of the strengthened glass-ceramics is 45000MPa / mm-64000MPa / mm; and / or, The surface compressive stress of the strengthened glass-ceramics is 350MPa-500MPa; and / or, The |CT_AV| of the strengthened glass-ceramics is 80MPa-110MPa.

10. The electronic product according to any one of claims 1 to 9, characterized in that: The microcrystalline glass is used in a display panel or display screen of an electronic product, and preferably the electronic product includes a mobile phone, a display, a tablet computer, an electronic watch, a smart bracelet, a smart watch, a television or smart glasses.

11. A glass-ceramic, characterized in that: The microcrystalline glass contains a crystal phase, and the main crystal phases in the crystal phase are lithium disilicate crystal phase and petalite crystal phase; In the microcrystalline glass, the molar percentage of SiO2 is 67.0%-71.0%, the molar percentage of Al2O3 is 3.5%-4.5%, the molar percentage of B2O3 is greater than 0 and less than or equal to 0.7%, the molar percentage of Na2O is greater than 0 and less than or equal to 1.0%, the molar percentage of K2O is greater than 0 and less than or equal to 0.50%, the molar percentage of P2O5 is 0.7%-1.5%, the molar percentage of ZrO2 is 2.0%-3.5%, and the molar percentage of CaO is greater than 0 and less than or equal to 1.8%; In terms of molar percentage, the component content of the microcrystalline glass satisfies: 10≥(Na2O+K2O+Li2O) / ZrO2≥5, preferably 9≥(Na2O+K2O+Li2O) / ZrO2≥7.

12. The glass-ceramic according to claim 11, characterized in that: In terms of molar percentage, the component content of the microcrystalline glass satisfies: 9≥(Na2O+K2O+Li2O) / ZrO2≥7, and / or, ZrO2+P2O5≥7.6×B2O3.

13. The glass-ceramics according to claim 11 or 12, characterized in that: In the glass-ceramics, the molar percentage of BaO is 0-0.8%, preferably the molar percentage of BaO is 0-0.50%, and the molar percentage of MgO is 0-1.0%, preferably the molar percentage of MgO is 0-0.80%; Preferably, in terms of molar percentage, the component content of the microcrystalline glass satisfies: CaO+BaO+MgO≥1.5×(Na2O+K2O), and / or the molar percentage ratio of (CaO+BaO+MgO) / ZrO2 is 0.2-0.7, preferably 0.2-0.5, and more preferably 0.2-0.

4.

14. The glass-ceramic according to any one of claims 11 to 13, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 67.0%-69.5%, and / or, The molar percentage of Al2O3 is 3.8%-4.3%, and / or, The molar percentage of Li2O is 20.0%-23.0%, and / or, The molar percentage of B2O3 is 0.01%-0.50%, and / or, The molar percentage of Na2O is 0.01%-0.8%, and / or, The molar percentage of K2O is 0.01% to 0.30%, and / or, The molar percentage of P2O5 is 0.9%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.5%, and / or, The molar percentage of CaO is 0.01%-1.5%.

15. The glass-ceramic according to claim 14, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 67.0%-68.0%, and / or, The molar percentage of Al2O3 is 4.0%-4.3%, and / or, The molar percentage of B2O3 is 0.01%-0.30%, and / or, The molar percentage of Na2O is 0.05%-0.3%, and / or, The molar percentage of K2O is 0.01%-0.20%, and / or, The molar percentage of P2O5 is 1.0%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.3%, and / or, The molar percentage of CaO is 0.10%-1.00%.

16. The glass-ceramic according to any one of claims 11 to 15, characterized in that: In the glass-ceramics, the average size of the grains is 10-50 nm, preferably 10-30 nm; and / or, In the microcrystalline glass, the crystalline phase accounts for at least 80.00 wt % of the microcrystalline glass, preferably 80 wt % to 97 wt % of the microcrystalline glass, and more preferably 85 wt % to 96 wt % of the microcrystalline glass.

17. The glass-ceramic according to any one of claims 11 to 16, characterized in that: When the thickness of the microcrystalline glass is 0.7 mm, for light with a wavelength of 550 nm, the microcrystalline glass is transparent and has a transmittance of not less than 90.00%, preferably not less than 90.20%, and more preferably not less than 90.40%.

18. The glass-ceramic according to any one of claims 11 to 17, characterized in that: After the microcrystalline glass is subjected to chemical strengthening treatment, a strengthened microcrystalline glass is obtained, and the strengthened microcrystalline glass includes a compressive stress layer formed by ion exchange.

19. The glass-ceramic according to claim 18, characterized in that: The depth DOL_0 of the compressive stress layer of the strengthened glass-ceramics is 15%-25% of the thickness of the glass-ceramics, preferably 20%-25%; and / or, The tensile stress linear density CT_LD of the strengthened glass-ceramics is 45000MPa / mm-64000MPa / mm; and / or, The surface compressive stress of the strengthened glass-ceramics is 350MPa-500MPa; and / or, The |CT_AV| of the strengthened glass-ceramics is 80MPa-110MPa.

20. The glass-ceramics according to claim 18 or 19, characterized in that: After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x4, x4<0.150 mg / cm 2 , preferably x4<0.100mg / cm 2 and / or, After standing in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x5, x5≤8.50mg / cm 2 ; and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x6 is, x6≤0.25 mg / cm 2 .

21. An electronic product, characterized in that: The electronic product comprises glass-ceramics, wherein the glass-ceramics comprises a crystal phase, wherein the main crystal phases in the crystal phases are lithium disilicate crystal phases and petalite crystal phases; In the microcrystalline glass, the molar percentage of SiO2 is 67.0%-71.0%, the molar percentage of Li2O is 20.0%-23.0%, the molar percentage ratio of SiO2 / (Li2O+Al2O3) is 2.5-3.0, preferably 2.5-2.8, the molar percentage of B2O3 is greater than 0 and less than or equal to 0.7%, the molar percentage of Na2O is greater than 0 and less than or equal to 1.0%, the molar percentage of K2O is greater than 0 and less than or equal to .50%, the molar percentage of P2O5 is 0.7%-1.5%, the molar percentage of ZrO2 is 2.0%-3.5%, and the molar percentage of CaO is greater than 0 and less than or equal to 1.8%; In terms of molar percentage, the component content of the microcrystalline glass satisfies: 10≥(Na2O+K2O+Li2O) / ZrO2≥5, preferably 9≥(Na2O+K2O+Li2O) / ZrO2≥7.

22. The electronic product according to claim 21, characterized in that: In terms of molar percentage, the component content of the microcrystalline glass satisfies: ZrO2+P2O5≥7.6×B2O3.

23. The electronic product according to claim 21 or 22, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 68.0%-71.0%, and / or, The molar percentage of Al2O3 is 3.5%-4.5%, and / or, The molar percentage of Li2O is 20.0%-22.0%, and / or, The molar percentage of B2O3 is 0.01%-0.50%, and / or, The molar percentage of Na2O is 0.01%-0.8%, and / or, The molar percentage of K2O is 0.01% to 0.30%, and / or, The molar percentage of P2O5 is 0.9%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.5%, and / or, The molar percentage of CaO is 0.01% to 1.5%, and / or, The molar percentage of BaO is 0-0.8%, and / or, The molar percentage of MgO is 0-1.0%.

24. The electronic product according to claim 23, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 69.0%-71.0%, and / or, The molar percentage of Li2O is 20.5%-21.5%, and / or, The molar percentage of B2O3 is 0.10%-0.40%, and / or, The molar percentage of Na2O is 0.1%-0.8%, and / or, The molar percentage of K2O is 0.01%-0.20%, and / or, The molar percentage of P2O5 is 0.9%-1.1%, and / or, The molar percentage of ZrO2 is 2.5%-3.3%, and / or, The molar percentage of CaO is 0.01%-0.10%.

25. The electronic product according to any one of claims 21 to 24, characterized in that: In the glass-ceramics, the average size of the grains is 10-50 nm, preferably 10-30 nm; and / or, In the microcrystalline glass, the crystalline phase accounts for at least 80.00 wt % of the microcrystalline glass, preferably 80 wt % to 97 wt % of the microcrystalline glass, and more preferably 85 wt % to 96 wt % of the microcrystalline glass.

26. The electronic product according to any one of claims 21 to 25, characterized in that: When the thickness of the microcrystalline glass is 0.7 mm, for light with a wavelength of 550 nm, the microcrystalline glass is transparent and has a transmittance of not less than 90.00%, preferably not less than 90.20%, and more preferably not less than 90.40%.

27. The electronic product according to any one of claims 21 to 26, characterized in that: After the microcrystalline glass is subjected to chemical strengthening treatment, a strengthened microcrystalline glass is obtained, and the strengthened microcrystalline glass includes a compressive stress layer formed by ion exchange.

28. The electronic product according to any one of claims 21 to 27, characterized in that: The depth DOL_0 of the compressive stress layer of the strengthened glass-ceramics is 15%-25% of the thickness of the glass-ceramics, preferably 20%-25%; and / or, The tensile stress linear density CT_LD of the strengthened glass-ceramics is 45000MPa / mm-64000MPa / mm; and / or, The surface compressive stress of the strengthened glass-ceramics is 350MPa-500MPa; and / or, The |CT_AV| of the strengthened glass-ceramics is 80MPa-110MPa.

29. The electronic product according to any one of claims 21 to 28, characterized in that: The microcrystalline glass is used in a display panel or display screen of an electronic product, and preferably the electronic product includes a mobile phone, a display, a tablet computer, an electronic watch, a smart bracelet, a smart watch, a television or smart glasses.

30. A glass-ceramic, characterized in that: The microcrystalline glass contains a crystal phase, and the main crystal phases in the crystal phase are lithium disilicate crystal phase and petalite crystal phase; In the glass-ceramics, the molar percentage of SiO2 is 67.0%-71.0%, the molar percentage of Li2O is 20.0%-23.0%, the molar percentage ratio of SiO2 / (Li2O+Al2O3) is 2.5-3.0, preferably 2.5-2.8, the molar percentage of B2O3 is greater than 0 and less than or equal to 0.7%, the molar percentage of Na2O is greater than 0 and less than or equal to 1.0%, the molar percentage of K2O is greater than 0 and less than or equal to 0.50%, the molar percentage of P2O5 is 0.7%-1.5%, the molar percentage of ZrO2 is 2.0%-3.5%, and the molar percentage of CaO is greater than 0 and less than or equal to 1.8%; In terms of molar percentage, the component content of the microcrystalline glass satisfies: 10≥(Na2O+K2O+Li2O) / ZrO2≥5, preferably 9≥(Na2O+K2O+Li2O) / ZrO2≥7.

31. The glass-ceramic according to claim 30, characterized in that: In terms of molar percentage, the component content of the microcrystalline glass satisfies: ZrO2+P2O5≥7.6×B2O3.

32. The glass-ceramics according to claim 30 or 31, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 68.0%-71.0%, and / or, The molar percentage of Al2O3 is 3.5%-4.5%, and / or, The molar percentage of Li2O is 20.0%-22.0%, and / or, The molar percentage of B2O3 is 0.01%-0.50%, and / or, The molar percentage of Na2O is 0.01%-0.8%, and / or, The molar percentage of K2O is 0.01% to 0.30%, and / or, The molar percentage of P2O5 is 0.9%-1.3%, and / or, The molar percentage of ZrO2 is 2.5%-3.5%, and / or, The molar percentage of CaO is 0.01% to 1.5%, and / or, The molar percentage of BaO is 0-0.8%, and / or, The molar percentage of MgO is 0-1.0%.

33. The glass-ceramic according to claim 32, characterized in that: In the glass-ceramics, the molar percentage of SiO2 is 69.0%-71.0%, and / or, The molar percentage of Li2O is 20.5%-21.5%, and / or, The molar percentage of B2O3 is 0.10%-0.40%, and / or, The molar percentage of Na2O is 0.1%-0.8%, and / or, The molar percentage of K2O is 0.01%-0.20%, and / or, The molar percentage of P2O5 is 0.9%-1.1%, and / or, The molar percentage of ZrO2 is 2.5%-3.3%, and / or, The molar percentage of CaO is 0.01%-0.10%.

34. The glass-ceramic according to any one of claims 30 to 33, characterized in that: In the glass-ceramics, the average size of the grains is 10-50 nm, preferably 10-30 nm; and / or, In the microcrystalline glass, the crystalline phase accounts for at least 80.00 wt % of the microcrystalline glass, preferably 80 wt % to 97 wt % of the microcrystalline glass, and more preferably 85 wt % to 96 wt % of the microcrystalline glass.

35. The glass-ceramic according to any one of claims 30 to 34, characterized in that: When the thickness of the microcrystalline glass is 0.7 mm, for light with a wavelength of 550 nm, the microcrystalline glass is transparent and has a transmittance of not less than 90.00%, preferably not less than 90.20%, and more preferably not less than 90.40%.

36. The glass-ceramic according to any one of claims 30 to 35, characterized in that: After the microcrystalline glass is subjected to chemical strengthening treatment, a strengthened microcrystalline glass is obtained, and the strengthened microcrystalline glass includes a compressive stress layer formed by ion exchange.

37. The glass-ceramic according to any one of claims 30 to 36, characterized in that: The depth DOL_0 of the compressive stress layer of the strengthened glass-ceramics is 15%-25% of the thickness of the glass-ceramics, preferably 20%-25%; and / or, The tensile stress linear density CT_LD of the strengthened glass-ceramics is 45000MPa / mm-64000MPa / mm; and / or, The surface compressive stress of the strengthened glass-ceramics is 350MPa-500MPa; and / or, The |CT_AV| of the strengthened glass-ceramics is 80MPa-110MPa.

38. The glass-ceramics according to claim 36 or 37, characterized in that: After standing at 95°C for 24 hours in a 5% hydrochloric acid solution, the weight loss per unit area of ​​the microcrystalline glass is x4, x4<0.150 mg / cm 2 , preferably x4<0.100mg / cm 2 and / or, After standing in a hydrofluoric acid solution with a mass concentration of 10% at 20°C for 20 minutes, the weight loss per unit area of ​​the microcrystalline glass is x5, x5≤8.50mg / cm 2 ; and / or placed in a sodium hydroxide solution with a mass concentration of 5% at 95° C. for 6 hours, the weight loss per unit area of ​​the microcrystalline glass x6 is, x6≤0.25 mg / cm 2 .

39. A method for preparing glass-ceramics, characterized in that: The steps include: (1) Preparation of substrate glass: Mixing various raw materials into a melt and forming the mixture, and then annealing the mixture to obtain substrate glass; (2) Preparation of glass-ceramic bricks: heating the substrate glass obtained in step (1) to perform nucleation treatment and crystallization treatment in sequence to obtain glass-ceramic bricks; (3) Cold working: The glass-ceramic brick obtained in step (2) is subjected to cold working to obtain a glass-ceramic sample as described in any one of claims 11 to 17 or a glass-ceramic sample as described in any one of claims 30 to 35.

40. The preparation method according to claim 39, characterized in that: The following steps are also included: (4) chemically strengthening the glass-ceramic sample obtained in step (3) to obtain the glass-ceramic sample as described in any one of claims 18 to 20 or the glass-ceramic sample as described in any one of claims 36 to 38.

41. The preparation method according to claim 39 or 40, characterized in that: In step (1), the melting temperature is 1500°C to 1650°C; and the annealing temperature is 450°C to 550°C.

42. The preparation method according to claim 39 or 40, characterized in that: In step (2), the nucleation treatment is performed at 530-565° C. for 90-240 min; and the crystallization treatment is performed at 640-700° C. for 90-240 min.

43. The preparation method according to claim 39 or 40, characterized in that: In step (2), the crystallization treatment is a semi-crystallization treatment. After the semi-crystallization treatment makes the degree of crystallization of the substrate glass reach 1 / 3 to 4 / 5 of the degree of complete crystallization, a 3D hot bending treatment is further performed to obtain microcrystalline glass; preferably, the 3D hot bending treatment is a hot bending treatment with three stages: preheating at a temperature of 450 to 720°C, hot bending at 720 to 820°C, and cooling to room temperature.

44. The preparation method according to claim 40, characterized in that In step (4), the chemical strengthening treatment is carried out in a mixed salt bath containing 30-100wt% NaNO3, preferably 30-90wt% NaNO3 and / or 0-70wt% KNO3, preferably 10-70wt% KNO3, and LiNO3 is added in an amount of 0.01-0.10wt% relative to the total weight of the mixed salt bath.

45. The preparation method according to claim 44, characterized in that: The chemical strengthening treatment performs one or more ion exchanges, so that the tensile stress line density CT_LD of the microcrystalline glass reaches 45000-64000 MPa / mm.

46. ​​A display screen, characterized in that: The display screen includes the micro-ceramic glass according to any one of claims 11 to 20 or the micro-ceramic glass according to any one of claims 30 to 38.

47. A display panel, characterized in that: The display panel includes the micro-ceramic glass according to any one of claims 11 to 20 or the micro-ceramic glass according to any one of claims 30 to 38.

48. A glass device, characterized in that: The glass device comprises the micro-ceramic glass according to any one of claims 11 to 20 or the micro-ceramic glass according to any one of claims 30 to 38.

Citation Information

Patent Citations

  • Glass ceramic with high elasticity modulus, and reinforced glass ceramic and preparation method thereof

    CN111087174A

  • Microcrystalline glass, microcrystalline glass product and manufacturing method thereof

    CN113387586A

  • Glass ceramic and preparation method thereof

    CN114605074A

  • Glass ceramic, tempered glass and preparation method and application thereof

    CN114671618A